Rainwater harvesting system for boarding schools: A water supply alternative for students' dormitory of Hira' Secondary school Jeram, Kuala Selangor / Sabariah Arbai … [et al.] - Arbai, Sabariah; Wan Kamaruddin, Wan Zarina; Kantasamy, Nesamalar; Sulaiman, Fuziah (2004)
Malaysia is a country gifted with abundant rainfall that is unevenly distributed in spartial chronological. This could be related to the consequences of various parts of the country occasionally afflicted with floods and water shortages. Nearly half of the country's population living in rural areas is still without sufficient piped water supply. The fact that water supply is a low budget priority in the previous Malaysia plans and the increasing number of urbanization being carried out which is unfortunately not parallel to some places has contributed to the water shortages. Schools, as one of the educational institutions in Malaysia, are a major scope of concern in which all the aspects of comfortability must be fulfil1. One solution is to ensure there is always a continuous water supply for the schools during the dry Season. To ascertain this situation, there is a need to identify a proper water catchment, storage area as well as a delivery system within the school compound. This study involves the process of identifying the layout of the school's compound and determines the most suitable catchment area for an appropriate design. The rainfall distribution of the surrounding area must be obtained to analyze the total amount of collectable rainfall. Then, the quality of the rainwater is tested in order to determine whether the rainwater can be used for non-portable usage. Lastly, this study would propose the procedure in providing an adequate rainwater harvesting system in schools.